1978
DOI: 10.1515/znb-1978-0322
|View full text |Cite
|
Sign up to set email alerts
|

New Alkaloids from Prosopis juliflora DC

Abstract: Abstract Prosopis juliflora, Piperidine Alkaloids The isolation of three new alkaloids from Prosopis julifiora is reported. A structure for the minor alkaloid julifloridine is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

1980
1980
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 1 publication
0
21
0
1
Order By: Relevance
“…It is an important species because of its high nitrogen fixing potential in very dry areas and in drought seasons and also it provides shelter and food to many species of animals on its nectar, pollen, leaves and fruits (Almaraz-Abarca et al, 2007), P. juliflora are rich source of piperidine alkaloids. Many alkaloids such as juliflorine, julifloricine and julifloridine (Ahmad et al, 1978), juliprosine (Daetwyler et al, 1981), juliprosinene and juliflorinine , 3'-oxojuliprosopine, sceojuliprosopino l, 3-oxojuliprosine and 3'-oxojuliprosine (Nakano et al, 2004) have been isolated from leaves and have proven to be pharmacologically active Aqeel et al, 1989), P. juliflora is used as a traditional medicine on different continents for curing catarrh, colds, diarrhea, dysentery, excrescences, flu, hoarseness, inflammation , measles, sore throat, and for the healing of wounds (Hartwell, 1971). Its juice is used in folk remedies for the cancerous condition.…”
Section: Introductionmentioning
confidence: 99%
“…It is an important species because of its high nitrogen fixing potential in very dry areas and in drought seasons and also it provides shelter and food to many species of animals on its nectar, pollen, leaves and fruits (Almaraz-Abarca et al, 2007), P. juliflora are rich source of piperidine alkaloids. Many alkaloids such as juliflorine, julifloricine and julifloridine (Ahmad et al, 1978), juliprosine (Daetwyler et al, 1981), juliprosinene and juliflorinine , 3'-oxojuliprosopine, sceojuliprosopino l, 3-oxojuliprosine and 3'-oxojuliprosine (Nakano et al, 2004) have been isolated from leaves and have proven to be pharmacologically active Aqeel et al, 1989), P. juliflora is used as a traditional medicine on different continents for curing catarrh, colds, diarrhea, dysentery, excrescences, flu, hoarseness, inflammation , measles, sore throat, and for the healing of wounds (Hartwell, 1971). Its juice is used in folk remedies for the cancerous condition.…”
Section: Introductionmentioning
confidence: 99%
“…(Fabaceae) is widespread in Saudi Arabia, USA and India (Kirtikar & Basu 1975). The plant is known for its medicinal value and many alkaloids such as juliflorine, julifloricine and julifloridine (Ahmad et al 1978), juliprosine (Daetwyler et al 1981), juliprosinine and juliflorinine (Ahmad et al 1989a(Ahmad et al , 1989b, benzene insoluble alkaloidal fraction (containing two major and three minor alkaloids) (Ahmad et al 1989a(Ahmad et al , 1989b have been isolated and their biological activities in vitro have been demonstrated. The present study reports the antibacterial activity of the alkaloid fraction of P. juliflora against important phytopathogenic Xanthomonas pathovars viz., Xanthomonas axonopodis pv.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, ketene elimination could lead to the ion at m / z 250 (pathway X). A series of ethylene eliminations from the ions at m / z 282 (pathway XI) and 268 (pathway XII) have been proposed . The fragment ion at m / z 43 (pathway XIII) also correlated with an acylium ion from the parent structure.…”
Section: Resultsmentioning
confidence: 99%